Experiences of women receiving childbirth care from public health facilities in Kumasi, Ghana. (December 2017) - Millicent Dzomeku, Veronica; van Wyk, Brian; Lori, Jody R.
Abstract: Objective: to explore women's experiences with childbirth care in Kumasi, Ghana. Design: exploratory, qualitative research design using in-depth interviews and content analysis. Setting: four public health facilities in Kumasi, Ghana. Participants: fifty-six women attending either antenatal or postnatal care at the four public health facilities. Measurements and findings: individual in-depth interviews were used to explore women's experiences with childbirth care. Mothers had both encouraging and discouraging experiences during care, which influenced their willingness to seek assisted health care during childbirth in the future. Participants who had experiences of empathetic support and continuous labour support and attention reported these to be encouraging. Other participants reported discouraging experiences such as disrespectful care and inadequate communication and involvement in care decisions . Key conclusions: Women in our study wanted to be seen as partners in the care process and not subordinate to care providers. Implications for practice: Midwives and student midwives must be given the tools and support to deliver patient-centred childbirth care. Highlights: Mothers experiences influenced their future use of the facility. Participants who had experiences of empathetic support and continuous labour support and attention reported these to be encouraging. Other participants reported discouraging experiences such as disrespectful care and inadequate. There is a need to explore obstacles to the provision of patient-centered care that would give mothers positive experiences of childbirth care.